Project Management Information System: the Role and the Issues of Implementation - Dumitru OPREA; Gabriela MESNITA (Informatică economică, 2006)
We are coping more and more with the project and project management in day by day life. Even if some activities are the similarly with common organization actions, the life cycle project activities request more information and more actions. So it is necessary to have some tools, methods and rules to manage a large amount of information which must be disseminated to numerous stakeholders. This need could be solved by project management information systems (PMIS). PMIS is a complex one, with various components which are depending on type of project, type of organization etc. The latest evolution of information and communication technology was favorable to our research field. Therefore, there are different tools to support the structure, automation and efficiency of PMIS. Moreover from several years it is spread the following notions: web-based project management, project management office, enterprise project management. So, we can see the fast evolution of this field. But, our paper will bring general ideas relating to project management information systems, like definition of PMIS, the project life cycle and the information needed of each stage, various tools to support the PMIS procedures. The characteristics, tools, trends will be our future research.